PENGGUNAAN MAJAS METAFORA DAN SIMILE DALAM KUMPULAN PUISI KUJILAT MANIS EMPEDU - Ardhita, Wenny Indah; Hermawan, Wawan; Fatoni, Akhmad (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
This research aims to examine the use of metaphors and similes in the collection of modern Indonesian poetry "Kujilat Manis Empedu" by D. Zawawi Imron. This research uses qualitative methods, which aim to gain an in-depth understanding of the use of language styles in poetry. The qualitative descriptive method is applied by grouping research data into several categories for analysis. The analysis shows that metaphors are used effectively to convey social and moral messages, describing the social conditions of the Madurese people and the life challenges they face. The use of metaphors makes poetry more imaginative and interesting, in accordance with the main purpose of metaphors in poetry, namely to produce beauty and richness of language. Apart from that, the use of similes has also proven effective in creating vivid images and conveying deep meaning. Similes are used to communicate complex feelings and thoughts in a beautiful and suggestive way. This research confirms that the use of metaphors and similes in poetry can enrich the poetic text and provide a more touching reading experience.Keywords: Figures of speech, metaphors, similes, Qualitative Study